Sikap Peserta Diklat PIM Tingkat IV terhadap Model Pembelajaran Blended Learning - Ratnaningsih Hidayati; Nadya Megawati Rachman; Caterin Magdalena Simamora (Universitas Mathla'ul Anwar Banten, 2021)
ATTITUDES OF LEVEL IV PIM TRAINING PARTICIPANTS TOWARDS BLENDED LEARNING LEARNING MODEL. The development of Information Technology is one of the driving forces behind e-government adoption. Nevertheless, the learning process of Government officials capability creation is already conceivably undertaken electronically. This study aims to discover perceptions of government officials towards mixed learning in year 2018 group of 40 DIKLAT PIM IV training participants. This research takes a quantitative approach using descriptive statistics and Analysis of Variance as analysis tool. The T-test tested the first testing hypotheses. A one-way ANOVA was conducted to test second hypotheses. The outcome indicates a constructive attitude towards blended learning among DIKLAT PIM IV 2018 training participants. Gender-based attitudes about blended learning are substantially different.